Odpowiedzi

2010-01-22T19:03:11+01:00
6x-18 > 8x - 14
6x -8x > 18 -14
-2x > 4 / (-2)
x < 2

2x-(6+x)≥0
2x-6-x> 0
2x-x > 6
1x > 6 / 1
X > 6

2) 3(x+1)/2-3>2(x-1)-x
3x + 3 : 1 > 2x - 2 -x
3x+3 > 2x -2 - x
3x -2x +x > -3-2
2x > -5 / 2
x > -2,5






Najlepsza Odpowiedź!
2010-01-22T19:05:18+01:00
1)
3(2x-6)>8x-14
6x-18>8x-14
-2x>4 //(-2)
x<2 zmieniam znam w drugą stronę bo dzielę przez '-'
x∈(-∞,2)

2)
2x-(6+x)≥0
2x-6-x≥0(zmieniam znaki bo jest minus przed nawiasem)
x≥6
x∈<6,∞)

3)
3(x+1)/2-3>2(x-1)-x
3x+3/-1>x-1-x
-3x-3>-1
-3x>2 //: (-3)
x< -⅔
x(-∞,-⅔)